Computational simulations of ZnO@GaN and GaN@ZnO core@shell nanotubes - Marana, N. L. [UNESP]; Casassa, S.; Longo, E.; Sambrano, J. R. [UNESP] (Elsevier, 2018)
The structural, electronic, and mechanical properties of armchair and zigzag chiralities double-walled and core@shell ZnO@GaN and GaN@ZnO nanotubes were investigated by periodic DFT/B3LYP calculations with an all-electron basis set. For both chiralities, GaN@ZnO presents minor strain and deposition energies, which predict that this nanotube can be easier formed and the GaN is the most favorable substrate (the core) than ZnO. On the other hand, the zigzag GaN@ZnO did not exhibit the major piezoelectric response, which is three times smaller than the ZnO@GaN nanotube, showing that the compression of the core@shell nanotube length is not favorable to this property. However, the piezoelectricity can be improved when the zigzag GaN@ZnO is under elongation. The elastic constants showed that the core@shell nanotubes are more rigid than the homogenous nanotubes and present higher piezoelectric constants. In addition, the projected DOS shows that GaN@ZnO has a type-II interface and ZnO@GaN has a type-I interface. Based on the results obtained from our theoretical models, the nanotubes have great potential for the experimental development of new electronic devices.
Keywords: Core@shell; Double-walled; Interface; Nanotube